Mathematical modelling of a photoelectrochemical anion exchange membrane electrolyser for sustainable hydrogen production - Tarique, Altaf Hasan; Prasad, Vivek; Khan, Sher Afghan; Khalid, Farrukh; Azmi, Mohd Hanafi (Elsevier Ltd, 2025)
Solar hydrogen production using a photoelectrochemical anion exchange membrane reactor is vital to reduce our dependence on fossil fuels. Anion exchange membranes use electrocatalysts based on low-cost earth metals. This paper provides a mathematical model to understand the influence of operating parameters on a photoelectrochemical anion exchange membrane reactor using Engineering Equation Solver (EES). It is used to estimate the performance of a reactor with hydrogen mass flow rate, energy, and exergy efficiency. The results indicate the highest hydrogen production of 75.92 μg/s at a solar irradiation flux of 600 W/m2. Overall energy efficiency decreases as the photocathode illumination area increases while the mass flow rate of hydrogen increases. Moreover, with the change in illuminated area from 0.04 to 0.08 m2, the overall efficiency decreases from 12.32% to 10.76%. Mathematical modelling indicates that the mass flow rate of hydrogen is directly proportional to the solar irradiation flux, illuminated area, and quantum efficiency